2017
DOI: 10.1111/1744-7917.12483
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide identification, characterization and evolution of cuticular protein genes in the malaria vector Anopheles sinensis (Diptera: Culicidae)

Abstract: Thirteen cuticular protein (CP) families have been recognized in arthropods. In this study, 250 Anopheles sinensis CP genes were identified and named based on genome and transcriptome sequences. They were classified into 10 families based on motifs and phylogenetic analyses. In 11 other insect species, nine had CP numbers > 150 while Apis mellifera and Tribolium castaneum had CP numbers less than 52. The CPs of eight species occupied > 1.4% of the total genomic gene number, whereas in three species the CPs occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
1
13
1
Order By: Relevance
“…For example, genome analysis suggested 238 putative cuticular proteins, including 136 CPR cuticular proteins in An. sinensis , which is slightly different from what reported by another group (Liu et al, 2017).…”
Section: Insect Cuticular Proteinscontrasting
confidence: 97%
See 1 more Smart Citation
“…For example, genome analysis suggested 238 putative cuticular proteins, including 136 CPR cuticular proteins in An. sinensis , which is slightly different from what reported by another group (Liu et al, 2017).…”
Section: Insect Cuticular Proteinscontrasting
confidence: 97%
“…Twenty eight cuticular proteins in CPR family have been reported in Apis mellifera (Consortium, 2006), 101 CPR cuticular protein genes reported in Drosophila melanogaster (Karouzou et al, 2007), 156 CPR genes identified in Anopheles gambiae (Cornman et al, 2008), 148 cuticular proteins in Bombyx mori (Futahashi et al, 2008), and 158 CPR cuticular protein genes identified and named in An. sinensis (Liu et al, 2017). Total cuticular proteins of A. mellifera, Dr. melanogaster, An.…”
Section: Insect Cuticular Proteinsmentioning
confidence: 99%
“…With the increasing of mosquito omics data, the diversity, characterization and functional analyses of a given group of genes are progressively increasing (He et al ., ; Liu et al ., ; Mei et al ., ; Wang et al ., ; Wu et al ., ; Yan et al ., ). However, the in silico SSR identification and analysis are relatively insufficient, and therefore the SSR features and the association with different species of mosquito genomes are still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…albopictus (Chen et al, 2015) have been sequenced and annotated, and more recently 16 Anopheles genomes have been reported (Neafsey et al, 2015). A number of transcriptomes and mitochondrial genomes have also been sequenced and comparatively analyzed (e.g., Chen et al, 2014;Hua et al, 2016;Hao et al, 2017;Fang et al, 2018) With the increasing of mosquito omics data, the diversity, characterization and functional analyses of a given group of genes are progressively increasing (He et al, 2016;Liu et al, 2018;Mei et al, 2018;Wang et al, 2018;Wu et al, 2018;Yan et al, 2018). However, the in silico SSR identification and analysis are relatively insufficient, and therefore the SSR features and the association with different species of mosquito genomes are still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…MUSCLE alignment of the predicted domain sequences indicated that the protein sequences of the 23 CP genes were highly similar, having 24 identical amino acid residues (Figure d). Protein family analysis based on the CuticleDB indicated that the 23 CP genes all belonged to RR2 subfamily and all presented a sequence motif that was homologous to the RR‐2 motif reported in Anopheles sinensis (Figure e; Liu et al, ).…”
Section: Resultsmentioning
confidence: 72%